Spray Drying Technique for Drying of Agricultural Product - Praneetpolkrang , Pothong (Recent Science and Technology, 2020)
Each year Thailand produces a large number of fresh and dry agricultural products. Post-harvest processing is an important process because it increases the value of agricultural products. Fruit and vegetables are often processed into powder products for beverages and this is an interesting form of product processing. The objective of this article is to study the drying of agricultural products using spray drying techniques. First, the study introduces the spray drying principle, and the heat and mass transfer of spray drying to analyze the heat transfer process, and how the drying process is controlled. The study then continues to investigate the factors that affect the quality of powder food products. Finally, the paper concludes with an application of the spray drying technique combined with other drying techniques.